A method for preparing a catalyst-coated membrane with high gas transmission and high proton conductivity for a fuel cell

By using perfluorosulfonic acid ionomer-coated porous carbon nanocages and hydroxyl-functionalized ionic liquid-impregnated Pt/C catalyst in the fuel cell catalytic layer, the problems of dense pore structure and slow proton conduction of the catalytic layer are solved, achieving It achieves high gas transmission and proton conduction, improving the performance of fuel cells.

CN118553928BActive Publication Date: 2025-01-21海卓健新能源材料(上海)有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410602087.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-15
Publication Date
2025-01-21
Estimated Expiration
2044-05-15

AI Technical Summary

Technical Problem

The pore structure of the catalytic layer of the existing proton exchange membrane fuel cell catalyst-coated film is dense, hindering the transmission of reaction gas, and the slow conduction of protons to the Pt active site in the carbon support pore, limiting the energy conversion capability of the fuel cell.

Method used

By adding perfluorosulfonic acid ionomer-coated porous carbon nanocages to the catalytic layer and impregnating the Pt/C catalyst with hydroxyl-functionalized ionic liquid, the gas transmission and proton conductivity of the catalytic layer can be improved.

Benefits of technology

It achieves high gas transmission and high proton conduction of the catalyst-coated membrane, improving the power density and service life of the fuel cell, especially showing better performance under low humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118553928B_ABST
    Figure CN118553928B_ABST
Patent Text Reader

Abstract

A method for preparing a catalyst-coated membrane with high gas transmission and high proton conduction for a fuel cell, which relates to a method for preparing a catalyst-coated membrane for a fuel cell. It aims to solve the technical problems of slow reaction gas transmission in the catalytic layer of the existing fuel cell catalyst-coated membrane and slow proton conduction to the Pt active sites in the pores of the carbon carrier. This preparation method: 1. Prepare porous carbon nanocages; 2. Prepare porous carbon nanocages coated with perfluorosulfonic acid ionomers; 3. Prepare hydroxyl-functionalized ionic liquid 1‑(2‑hydroxyethyl)‑3‑methylimidazole bis(trifluoromethanesulfonyl)imide salt; 4. Prepare Pt / C catalyst impregnated with hydroxyl-functionalized ionic liquid; 5. Prepare slurry; 6. Catalytic layer coating and drying. The peak power density of the catalyst-coated membrane in a fuel cell is 1.592W / cm 2 , the current density reaches 4.390A / cm at 0.35V voltage 2 , which can be used in proton exchange membrane fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a catalyst coating membrane for a fuel cell. Background Art

[0002] In order to achieve the sustainable development strategy, the development and efficient utilization of clean energy such as hydrogen energy is imminent. Proton exchange membrane fuel cells are an important hydrogen energy conversion device that can directly convert hydrogen energy into electrical energy through electrochemical reactions, thereby achieving efficient energy conversion and utilization. In addition, proton exchange membrane fuel cells also have the advantages of zero carbon emissions, fast low-temperature start-up speed, and high reliability. These advantages make fuel cells very promising in the fields of automobiles, fixed power stations, aerospace, etc. Therefore, the research and development of fuel cells plays a vital role in the development of the hydrogen energy economy. However, during the operation of fuel cells, due to the slow gas transmission, proton conduction, and charge transfer reaction process, large polarization losses are caused, which limits the energy conversion capacity of fuel cells.

[0003] The membrane electrode is one of the core components of the proton exchange membrane fuel cell. It is mainly composed of a catalyst layer, a proton exchange membrane and a diffusion layer. The anode and cathode catalyst layers can provide reaction sites for the hydrogen oxidation reaction (HOR) and the oxygen reduction reaction (ORR), respectively. The composition and structure of the catalyst layer directly affect the electrochemical reaction rate and are the key to whether the fuel cell can achieve efficient energy conversion. At present, the most common catalyst layer is composed of Pt / C catalyst and perfluorosulfonic acid ionomer. The Pt / C catalyst can provide reaction active sites and reduce the energy barrier of the electrochemical reaction; the perfluorosulfonic acid ionomer serves as an electrolyte and provides a medium for proton conduction. In the traditional catalyst layer, the high-polymerization long-chain perfluorosulfonic acid ionomer is easy to form agglomeration, making the pore structure in the catalyst layer dense, hindering the supply of reaction gas to the active sites, and increasing the concentration polarization of the battery. In addition, the Pt particles of the Pt / C catalyst are mainly deposited in the small-sized mesopores of the carbon carrier. The Pt particles in the pores are far away from the ionomer, and the conduction of protons to the Pt particles in the pores can only be mediated by water. Under working conditions, the catalyst and the water in the electrolyte contact each other and form a double layer at the interface. However, due to the low ionic strength of water, the diffusion layer thickness of the double layer is large, making it difficult for positively charged protons to diffuse to the Pt surface. The large proton transfer resistance inhibits the electrode reaction rate and affects the battery performance. Especially under low humidity conditions, the limited water content in the electrode inhibits both the vehicle mechanism and the Grotthus mechanism of proton transfer, and the impact of the proton transfer resistance on battery performance becomes more prominent. Summary of the invention

[0004] The present invention aims to solve the technical problems that the internal pore structure of the catalyst layer of the existing proton exchange membrane fuel cell catalyst coating membrane is dense, which hinders the transmission of reaction gases and the protons are slowly conducted to the Pt active sites in the pores of the carbon carrier, and to provide a method for preparing a catalyst coating membrane with high gas transmission and high proton conduction for fuel cells. By improving the gas transmission and proton conduction capabilities inside the catalyst layer, the power density and service life of the proton exchange membrane fuel cell can be improved.

[0005] The method for preparing a catalyst-coated membrane with high gas transmission and high proton conductivity for a fuel cell of the present invention is carried out according to the following steps:

[0006] 1. Preparation of porous carbon nanocages:

[0007] (1) 1-hexadecylamine and CoCl2·6H2O are weighed in a beaker at a mass ratio of 1-hexadecylamine to CoCl2·6H2O of (2 to 2.5):1, and anhydrous ethanol is added to evenly disperse the mixture, and then the ethanol is completely evaporated to obtain a precursor;

[0008] (2) The precursor and KCl crystals are fully mixed by a ball mill, and then placed in a tube furnace, heated to 700-800° C. under an argon atmosphere, and maintained for 2-3 hours; after the reaction is completed, the product is cleaned with distilled water and anhydrous ethanol, and vacuum dried to obtain a Co / C nanocomposite material;

[0009] (3) immersing the Co / C nanocomposite material into a hydrochloric acid solution, stirring at 60° C. to 80° C. for 6 to 8 hours to completely dissolve the Co nanosheets, centrifuging and washing to remove impurities, and vacuum drying to obtain carbon nanocages;

[0010] (4) mixing the carbon nanocage and the pore-forming agent uniformly, placing them in a tube furnace, heating them to 800-900° C. in an argon atmosphere, and maintaining the temperature for 1-2 hours to fully pyrolyze the pore-forming agent and etch the carbon nanocage to obtain a porous carbon nanocage;

[0011] 2. Preparation of porous carbon nanocages coated with perfluorosulfonic acid ionomers:

[0012] (1) Weighing a porous carbon nanocage and a Nafion solution, placing them in a beaker, stirring at a temperature of 40 to 60° C. to fully mix the carbon nanocage and the perfluorosulfonic acid ionomer in the Nafion solution, and continuing to stir until the solvent in the Nafion solution is completely volatilized to obtain a solid mixture;

[0013] (2) placing the solid mixture in a tube furnace in an argon atmosphere and treating it at a temperature of 130 to 150° C. for 2 to 3 hours, so that the perfluorosulfonic acid ionomer is coated on the carbon nanocage to obtain a porous carbon nanocage coated with the perfluorosulfonic acid ionomer;

[0014] 3. Preparation of hydroxyl functionalized ionic liquid 1-(2-hydroxyethyl)-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt:

[0015] (1) Methylimidazole and 2-bromoethanol are mixed evenly at a molar ratio of 1:(1-1.2), added into a round-bottom flask, refluxed at 80-82° C. for 20-24 h, then the product is washed with ether to remove unreacted 2-bromoethanol, and then placed in an oven at 60° C. to 80° C. to dry for 40-48 h, to obtain an intermediate product, 1-(2-hydroxyethyl)-3-methylimidazolium bromide;

[0016] (2) lithium bis(trifluoromethanesulfonyl)imide and the intermediate product are weighed at a molar ratio of 1:1; lithium bis(trifluoromethanesulfonyl)imide and the intermediate product are respectively prepared into aqueous solutions; the aqueous solution of lithium bis(trifluoromethanesulfonyl)imide is then added to the aqueous solution of the intermediate product, and an ion exchange reaction is carried out at room temperature for 20 to 24 hours to obtain a mixture of ionic liquid and water; extraction is performed to separate the ionic liquid from the water in the mixture, and the ionic liquid is then washed with deionized water, and vacuum dried at room temperature for 24 to 48 hours to obtain a hydroxyl-functionalized ionic liquid 1-(2-hydroxyethyl)-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt;

[0017] 4. Preparation of Pt / C Catalyst Impregnated with Hydroxyl Functionalized Ionic Liquid:

[0018] (1) dispersing the hydroxyl-functionalized ionic liquid 1-(2-hydroxyethyl)-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt in isopropanol to prepare a 4-5 mg / mL ionic liquid solution;

[0019] (2) weighing a Pt / C catalyst and adding it to a beaker, then adding the ionic liquid solution prepared in step 4 (1), and ultrasonicating for 20 to 30 minutes to obtain a mixture; then stirring the mixture at a temperature of 45 to 55° C. to evaporate the solvent therein, so that the ionic liquid is fully impregnated into the pores of the Pt / C catalyst to obtain a powder; finally, vacuum drying the powder to obtain a Pt / C catalyst impregnated with a hydroxyl-functionalized ionic liquid;

[0020] 5. Configuration of catalyst slurry:

[0021] (1) Weighing a Pt / C catalyst impregnated with a hydroxyl-functionalized ionic liquid and a porous carbon nanocage coated with a perfluorosulfonic acid ionomer and placing them in a slurry dispersion tube, and adding an appropriate amount of deionized water to wet the catalyst and the porous carbon nanocage;

[0022] (2) adding Nafion solution and isopropanol to the slurry dispersion tube, and dispersing the mixture for 20 to 30 minutes using a high-speed shearing device to obtain a uniformly dispersed catalyst slurry;

[0023] 6. Coating and drying of the catalytic layer:

[0024] Ultrasonic spraying equipment is used to evenly spray the catalyst slurry on both sides of the proton exchange membrane to prepare the cathode and anode catalyst layers, thereby obtaining a catalyst-coated membrane with high gas transmission and high proton conductivity for fuel cells.

[0025] Furthermore, the concentration of the hydrochloric acid solution in step 1 (4) is 4-6M.

[0026] Furthermore, the pore-forming agent in step 1 (5) is one or more of ammonium chloride, melamine and cyanamide.

[0027] Furthermore, in step 2 (1), the mass percentage of the perfluorosulfonic acid ionomer in the Nafion solution is 5% to 20%.

[0028] Furthermore, in step 2 (1), the mass ratio of the porous carbon nanocage to the perfluorosulfonic acid ionomer in the Nafion solution is 1:(0.5-0.7).

[0029] Furthermore, in step four (2), the mass percentage of Pt in the Pt / C catalyst is 20% to 25%; and the mass ratio of the ionic liquid to the Pt / C catalyst is 1:(0.54 to 0.34).

[0030] Furthermore, the vacuum drying in step 4 (2) is carried out at a temperature of 30°C.

[0031] Furthermore, in step five (1), the mass ratio of the Pt / C catalyst impregnated with the hydroxyl-functionalized ionic liquid to the porous carbon nanocages coated with the perfluorosulfonic acid ionomer is (2-2.5):1.

[0032] Furthermore, in step five (2), the mass percentage of the perfluorosulfonic acid ionomer in the Nafion solution is 5% to 20%.

[0033] Furthermore, in step five (2), in the slurry, the mass ratio of the perfluorosulfonic acid ionomer to the Pt / C catalyst impregnated with the hydroxyl functionalized ionic liquid is (0.6-0.9):1.

[0034] Furthermore, in step 6 (1), the Pt loading in the cathode catalyst layer is 0.15-0.18 mg / cm 2 The Pt loading in the anode catalyst layer is 0.05-0.06 mg / cm 2 .

[0035] The preparation method of the present invention regulates the catalyst-coated membrane with high gas transmission and high proton conductivity for fuel cells from the following two aspects:

[0036] (1) From the perspective of material transfer: By adding porous carbon nanocages coated with perfluorosulfonic acid ionomers to the catalytic layer, a catalytic layer with a rich hierarchical porous structure and good gas transfer capacity was constructed. First, the carbon nanocages were coated with ionomers and the amount of ionomer added during the preparation of the catalyst slurry was reduced. This can reduce the ionomers wrapped on the surface of the Pt / C nanoparticles while ensuring the proton conduction of the catalytic layer, reduce the thickness of the ionomer film, and enhance the local oxygen mass transfer capacity. In addition, the hollow porous structure of the nanocage can provide a diffusion channel for the transmission of the reaction gas to the active site, improve the diffusion mechanism, increase the oxygen transfer flux, and alleviate the problem of dense pore structure and hindering oxygen transfer in the traditional catalytic layer due to the large agglomeration of perfluorosulfonic acid ionomers and Pt / C particles.

[0037] (2) Proton conduction perspective: The present invention innovatively uses hydroxyl-functionalized ionic liquid 1-(2-hydroxyethyl)-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt to impregnate the Pt / C catalyst, so that the ionic liquid fills the pores of the catalyst. The high ionic strength of the ionic liquid is used to reduce the thickness of the double layer at the Pt / electrolyte interface, provide a medium for proton conduction in the pores, and improve the accessibility of protons to the Pt particles in the pores. Compared with conventional ionic liquids, the cations of this ionic liquid contain hydroxyl functional groups, which can form a strong hydrogen bond network. Proton transfer is achieved through the formation and breaking of a series of hydrogen bonds between donors and acceptors, promoting the conduction rate of protons under the Grotthus mechanism, thereby further improving the proton conductivity of the catalytic layer. In addition, hydroxyl-functionalized ionic liquids have stronger interactions with water than non-functionalized ionic liquids, which can enhance the adaptability of membrane electrodes under low humidity conditions.

[0038] The present invention regulates material transfer and proton conduction respectively, and successfully prepares a high-performance fuel cell catalyst coating membrane. Compared with the traditional method, the catalyst coating membrane has an optimized material transfer and proton conduction path, effectively improves the mass transfer capacity and proton conductivity of the catalyst coating membrane, and enhances the performance of the fuel cell under normal conditions and low humidity conditions. In the fuel cell, under the same hydrogen-air conditions, the peak power density of the catalyst coating membrane of the present invention reaches 1.592W / cm 2 , which is 17.5% higher than the peak power density of the catalyst coating membrane prepared by the traditional method. In addition, at a voltage of 0.35V, the current density of the catalyst layer prepared by the present invention can reach 4.390A / cm 2The current density of the catalyst layer prepared by the traditional method is increased by 15.7%. The high-performance fuel cell catalyst layer of the present invention can be used in a single cell or a stack of a proton exchange membrane fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a comparison diagram of polarization curves and power density curves of Example 1 and Comparative Example 1.

[0040] Figure 2 It is a comparison diagram of hydrogen / air electrochemical impedance of Example 1 and Comparative Example 1.

[0041] Figure 3 It is a comparison diagram of hydrogen / nitrogen electrochemical impedance of Example 1, Comparative Example 2 and Comparative Example 3.

[0042] Figure 4 It is a comparison diagram of polarization curves and power density curves of Example 1 and Comparative Examples 2 and 3.

[0043] Figure 5 It is a comparison diagram of the low humidity polarization curves and power density curves of Example 1 and Comparative Examples 2 and 3.

[0044] Figure 6 Schematic diagram of the molecular dynamics simulation of the catalytic layer of Example 1; (a) is the main view; (b) is the top cross-sectional view.

[0045] Figure 7 This is a radial distribution function curve diagram of the molecular dynamics simulation of the catalyst layer in Example 1. DETAILED DESCRIPTION

[0046] Use the following examples to verify the beneficial effects of the present invention:

[0047] Example 1: The method for preparing a catalyst-coated membrane with high gas transmission and high proton conductivity for a fuel cell of this embodiment is carried out according to the following steps:

[0048] 1. Preparation of porous carbon nanocages:

[0049] (1) Weigh 1 g of 1-hexadecylamine and 400 mg of CoCl2·6H2O and place them in a beaker, then add 100 mL of anhydrous ethanol and ultrasonically treat for 20 min to uniformly disperse them, then stir at 60° C. to completely evaporate the ethanol, and then vacuum dry at 60° C. for 8 hours to obtain a precursor;

[0050] (2) The precursor and KCl crystals were fully mixed by a ball mill, and then placed in a tube furnace, heated to 700°C under an argon atmosphere, and maintained for 3 hours; after the reaction was completed, the product was washed with distilled water and anhydrous ethanol three times each, and vacuum dried at 60°C for 8 hours to obtain a Co / C nanocomposite material;

[0051] (3) immersing the Co / C nanocomposite material in a 6M hydrochloric acid solution, stirring at 80°C for 6 h to completely dissolve the Co nanosheets, centrifuging and washing three times to remove impurities, and vacuum drying at 80°C for 8 h to obtain carbon nanocages;

[0052] (4) 100 mg of carbon nanocages and 200 mg of ammonium chloride powder were mixed evenly, placed in a tube furnace, heated to 900° C. under an argon atmosphere, and maintained for 1 hour to fully pyrolyze the ammonium chloride and etch the carbon nanocages to obtain porous carbon nanocages;

[0053] 2. Preparation of porous carbon nanocages coated with perfluorosulfonic acid ionomers:

[0054] (1) adding 100 mg of porous carbon nanocages and 1160 mg of a Nafion solution with a mass percentage concentration of 5% into a beaker, stirring rapidly at 800 rpm at 60° C. to fully mix the carbon nanocages and the perfluorosulfonic acid ionomer in the Nafion solution, and continuing stirring until the solvent in the Nafion solution is completely volatilized to obtain a solid mixture;

[0055] (2) placing the solid mixture in a tube furnace in an argon atmosphere and treating it at a temperature of 130° C. for 2 h, so that the perfluorosulfonic acid ionomer is tightly coated on the carbon nanocage to obtain a porous carbon nanocage coated with the perfluorosulfonic acid ionomer;

[0056] 3. Preparation of hydroxyl functionalized ionic liquid 1-(2-hydroxyethyl)-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt:

[0057] (1) Methylimidazole and 2-bromoethanol were mixed uniformly in a molar ratio of 1:1.2, and then added into a round-bottom flask, refluxed at 80° C. for 24 h, and then the product was washed with ether to remove unreacted 2-bromoethanol, and then placed in an oven at 60° C. to dry for 48 h, to obtain an intermediate product, 1-(2-hydroxyethyl)-3-methylimidazole bromide;

[0058] (2) lithium bis(trifluoromethanesulfonyl)imide and the intermediate product are weighed at a molar ratio of 1:1; lithium bis(trifluoromethanesulfonyl)imide and the intermediate product are respectively prepared into aqueous solutions with a concentration of 0.1 mol / L; the aqueous solution of lithium bis(trifluoromethanesulfonyl)imide is then added to the aqueous solution of the intermediate product, and an ion exchange reaction is carried out at room temperature for 24 hours to obtain a mixture of ionic liquid and water; extraction is performed to separate the ionic liquid from the water in the mixture, and the ionic liquid is washed three times with deionized water, and vacuum dried at room temperature for 48 hours to obtain a hydroxyl-functionalized ionic liquid 1-(2-hydroxyethyl)-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt;

[0059] 4. Preparation of Pt / C Catalyst Impregnated with Hydroxyl Functionalized Ionic Liquid:

[0060] (1) dispersing the hydroxyl-functionalized ionic liquid 1-(2-hydroxyethyl)-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt in isopropanol to prepare an ionic liquid solution with a concentration of 5 mg / mL;

[0061] (2) Weighing 120 mg of a Pt / C catalyst having a mass percentage concentration of 20% Pt into a beaker, adding 10.4 mL of the ionic liquid solution prepared in step 4 (1), and ultrasonically treating for 30 min to obtain a mixture; stirring the mixture at a temperature of 50° C., evaporating the solvent therein to allow the ionic liquid to fully impregnate the pores of the Pt / C catalyst, and obtaining a powder; finally, vacuum drying the powder at a temperature of 30° C. for 8 hours to obtain a Pt / C catalyst impregnated with a hydroxyl-functionalized ionic liquid;

[0062] 5. Configuration of catalyst slurry:

[0063] (1) Weigh 165 mg of Pt / C catalyst impregnated with hydroxyl-functionalized ionic liquid and 79 mg of porous carbon nanocages coated with perfluorosulfonic acid ionomer and place them in a slurry dispersion tube, and add an appropriate amount of deionized water to wet the catalyst and porous carbon nanocages;

[0064] (2) adding 900 mg of 5% Nafion solution and 18 mL of isopropanol to the slurry dispersion tube, and dispersing the mixture for 30 min using a high-speed shearing device to obtain a uniformly dispersed catalyst slurry;

[0065] 6. Coating and drying of the catalytic layer:

[0066] The catalyst slurry was evenly sprayed on both sides of the proton exchange membrane using ultrasonic spraying equipment to prepare the cathode and anode catalyst layers, where the cathode Pt loading was 0.15 mg / cm 2 , the anode Pt loading is 0.05 mg / cm 2 , obtaining a catalyst-coated membrane with high gas transport and high proton conductivity for fuel cells.

[0067] Comparative Example 1: This comparative example is a conventional method for preparing a fuel cell catalyst coating membrane, and the specific steps are as follows:

[0068] 1. Catalyst slurry preparation:

[0069] (1) Weigh 115 mg of 20 wt.% Pt / C catalyst and place it in a slurry dispersion tube, and add an appropriate amount of deionized water to fully wet the catalyst;

[0070] (2) Add 1480 mg of 5 wt.% Nafion solution and 18 mL of isopropanol into the slurry dispersion tube, and disperse for 30 minutes using a high-speed shearing device to obtain a uniformly dispersed catalyst slurry.

[0071] 2. Preparation of catalyst coated membrane and membrane electrode:

[0072] The membrane electrode slurry was sprayed uniformly on both sides of the proton exchange membrane using ultrasonic spraying equipment, and the Pt loading of the cathode and anode was 0.15 mg / cm 2 and 0.05mg / cm 2 The catalytic layer was finally obtained to obtain a comparative catalyst coated membrane.

[0073] The catalyst coated membranes prepared in Example 1 and Comparative Example 1 and carbon paper were assembled into a fuel cell. The electrochemical performance test was carried out using the Qunyi 850e test system. The battery operating temperature was 80°C, the humidity was 100% RH, the hydrogen and air flow rates were 0.5 L / min and 2 L / min respectively, and the cathode and anode back pressures were both 100 kPa.

[0074] The polarization curves and power density curves of the membrane electrode of Example 1 and Comparative Example 1 are as follows: Figure 1 The test results show that Example 1 has higher performance than Comparative Example 1. The peak power densities of Example 1 and Comparative Example 1 are 1.592 W / cm 2 and 1.355W / cm 2 , the current density at 0.35V is 4.390A / cm 2 and 3.795A / cm 2 , which shows that Example 1 uses carbon nanocages to optimize the catalytic layer structure and uses hydroxyl-functionalized ionic liquids to modify the catalyst, thereby effectively improving the mass transfer and proton conduction capabilities, alleviating polarization losses, and achieving improved fuel cell performance.

[0075] The electrochemical impedance spectra of the membrane electrode of Example 1 and Comparative Example 1 are as follows: Figure 2 As shown, in both the low-frequency region and the high-frequency region, the membrane electrode of Example 1 exhibits a smaller impedance arc than that of Comparative Example 1, indicating that Example 1 effectively reduces the diffusion impedance and charge transfer impedance of the membrane electrode, further proving the beneficial effects of Example 1.

[0076] Comparative Example 2: This comparative example differs from Example 1 in that steps 3 and 4 are omitted, and the catalyst slurry preparation in step 5 is replaced by the following steps:

[0077] Catalyst slurry preparation:

[0078] (1) Weighing 115 mg of a Pt / C catalyst with a Pt mass percentage of 20% and 79 mg of a porous carbon nanocage coated with a perfluorosulfonic acid ionomer, placing them in a slurry dispersion tube, and adding an appropriate amount of deionized water to fully wet the catalyst and the porous carbon nanocage;

[0079] (2) adding 900 mg of 5% Nafion solution and 18 mL of isopropanol to the slurry dispersion tube, and dispersing the mixture for 30 min using a high-speed shearing device to obtain a uniformly dispersed catalyst slurry;

[0080] The other steps and parameters are the same as those in Example 1.

[0081] Comparative Example 3: This comparative example differs from Example 1 in that steps 3, 4, and 5 are replaced by the following steps:

[0082] 3. Preparation of ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt:

[0083] (1) First, methylimidazole and ethyl bromide are mixed uniformly in a molar ratio of 1:1.2, then added into a round-bottom flask, refluxed at 80°C for 24 hours, then the product is washed with ether three times to remove unreacted impurities, and then placed in an oven at 60°C for 48 hours to obtain an intermediate product, 1-ethyl-3-methylimidazole bromide;

[0084] (2) lithium bis(trifluoromethanesulfonyl)imide and 1-ethyl-3-methylimidazolium bromide are weighed in a molar ratio of 1:1; lithium bis(trifluoromethanesulfonyl)imide and 1-ethyl-3-methylimidazolium bromide are respectively prepared into aqueous solutions with a concentration of 0.1 mol / L; then the aqueous solution of lithium bis(trifluoromethanesulfonyl)imide is slowly added to the aqueous solution of 1-ethyl-3-methylimidazolium bromide, and an anion exchange reaction is carried out under stirring at room temperature for 24 hours to obtain a mixture of ionic liquid and water; extraction is performed to separate the ionic liquid from the water in the mixture, and the ionic liquid is washed three times with deionized water, and vacuum dried at room temperature for 48 hours to obtain the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide;

[0085] 4. Preparation of Pt / C catalyst impregnated with ionic liquid:

[0086] (1) dispersing the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt in isopropanol to prepare a 5 mg / mL ionic liquid solution;

[0087] (2) Weighing 120 mg of a Pt / C catalyst having a Pt content of 20% by mass into a beaker, adding 10.4 mL of the ionic liquid solution of step 4 (1), and ultrasonicating for 30 min to obtain a mixture; stirring the mixture at a temperature of 50° C., evaporating the solvent therein to allow the ionic liquid to fully impregnate the pores of the Pt / C catalyst, and obtaining a powder; finally, vacuum drying the powder at a temperature of 30° C. for 8 hours to obtain a Pt / C catalyst impregnated with an ionic liquid;

[0088] 5. Configuration of catalyst slurry:

[0089] (1) Weigh 165 mg of ionic liquid-impregnated Pt / C catalyst and 79 mg of porous carbon nanocages coated with perfluorosulfonic acid ionomer and place them in a slurry dispersion tube, and add an appropriate amount of deionized water to fully wet the catalyst and the porous carbon nanocages;

[0090] (2) Add 900 mg of 5% mass percent Nafion solution and 18 mL of isopropanol to the slurry dispersion tube. Use a high-speed shearing device to disperse for 30 minutes to obtain a uniformly dispersed catalyst slurry;

[0091] The other steps and parameters are the same as those in Example 1 to obtain a proton exchange membrane fuel cell membrane electrode.

[0092] The catalyst coated membranes prepared in Example 1, Comparative Example 2 and Comparative Example 3 were assembled with carbon paper into a fuel cell cell, and the electrochemical performance was tested using the Qunyi 850e test system. For the proton conduction impedance test, the test conditions were: temperature 80°C, humidity 100% RH, hydrogen and nitrogen flow rates of 0.5L / min and 0.5L / min, respectively, the test potential was 0.2V, the amplitude was 0.01V, and the frequency was 10000Hz-1Hz. The electrochemical impedance spectra of Example 1, Comparative Example 2 and Comparative Example 3 under H2 / N2 conditions are shown in Figure 1. Figure 3 According to the linear transmission model, the projection of the 45° linear region at high frequencies in the impedance spectrum on the real axis represents the proton conduction resistance (R H+ ). Figure 3 It can be seen that the R of the Pt catalyst membrane electrode modified with hydroxyl functionalized (Example 1) and non-functionalized (Comparative Example 3) ionic liquids is H+ The R values ​​of the Pt catalyst membrane electrode without ionic liquid modification (Comparative Example 2) are smaller than those of the Pt catalyst membrane electrode without ionic liquid modification, which proves that the use of ionic liquid to modify the catalyst can change the double electric layer structure in the catalyst pores, increase the accessibility of protons to the Pt surface, and improve the proton conduction of the membrane electrode. Comparing Example 1 with Comparative Example 3, it is found that the membrane electrode using hydroxyl functionalized ionic liquid has a smaller R value than the membrane electrode using non-hydroxyl functionalized ionic liquid. H+, demonstrating that under the action of hydroxyl functional groups, ionic liquids can promote proton conduction by enhancing the hydrogen bond network.

[0093] For the polarization curve test, the test conditions are: battery operating temperature 80°C, humidity 100% RH, hydrogen and air flow rates of 0.5L / min and 2L / min respectively, and cathode and anode back pressures of 100kPa. The polarization curves and power density curves of Example 1, Comparative Example 2, and Comparative Example 3 are shown in Figure 2. Figure 4 The test results show that Example 1 has higher performance than Comparative Example 3. The peak power densities of Example 1, Comparative Example 2 and Comparative Example 3 are 1.592 W / cm 2 , 1.436W / cm 2 , 1.466W / cm 2 , indicating that the use of ionic liquids to modify Pt catalysts can improve the proton conductivity of the catalytic layer and thus improve the power density of the fuel cell. In addition, the hydroxyl-functionalized ionic liquid of Example 1 exhibits better performance than Comparative Example 3 due to its stronger proton conductivity.

[0094] For the low humidity polarization curve test, the test conditions are: battery operating temperature 80°C, humidity 40% RH, hydrogen and air flow rates of 0.5L / min and 2L / min respectively, and cathode and anode back pressures of 100kPa. The low humidity performance curves of Example 1 and Comparative Examples 2 and 3 are shown in Figure 2. Figure 5 As shown. The peak power density of Example 1 is 0.179 W / cm 2 , higher than 0.161W / cm in Comparative Example 2 2 Compared with 0.158W / cm2 of Comparative Example 3 2 It is proved that Example 1 effectively improves the low-humidity performance of the fuel cell through the hydrogen bond network of the hydroxyl functionalized ionic liquid and the interaction with water.

[0095] For molecular dynamics simulations, the Pt(111) layer was used as the substrate, and the anions and cations of 1-(2-hydroxyethyl)-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (HOEMImNTf2) were randomly distributed on the Pt plane. Then, ionomers (PSFA), hydronium ions (H3O + ), water (H2O), to simulate the microenvironment of the catalytic layer modified with hydroxyl functionalized ionic liquid. The model structure is as follows Figure 6 , calculate the radial distribution function of the hydroxyl oxygen of 1-(2-hydroxyethyl)-3-methylimidazolium ion (HOEMIm+) and oxygen in water as follows Figure 7 As shown, the results show A main peak appears at the position of The hydroxyl oxygen of the 1-(2-hydroxyethyl)-3-methylimidazolium cation and the oxygen in water can act as donors and acceptors of hydrogen atoms, providing conditions for the transmission of protons in the microscopic reaction zone of the catalytic layer.

[0096] The present invention uses porous carbon nanocages to improve the pore structure of the catalyst layer, and uses a Pt / C catalyst impregnated with a hydroxyl functionalized ionic liquid to improve the proton conduction of the catalyst layer, thereby preparing a fuel cell catalyst coating membrane with high performance in both high and low humidity environments. Compared with the traditional method, the catalyst coating membrane has an optimized hierarchical porous mass transfer channel and proton transport network, which effectively improves the mass transfer efficiency and proton conduction capacity of the reaction gas, and enhances the performance of the catalyst coating membrane.

Claims

1. A method for preparing a catalyst-coated membrane with high gas transport and high proton conductivity for a fuel cell, characterized in that The method proceeds as follows:

1. Preparation of porous carbon nanocages: (1) 1-hexadecylamine and CoCl2·6H2O are weighed in a beaker at a mass ratio of 1-hexadecylamine to CoCl2·6H2O of (2 to 2.5):1, and anhydrous ethanol is added to evenly disperse the mixture, and then the ethanol is completely evaporated to obtain a precursor; (2) The precursor and KCl crystals are fully mixed by a ball mill, and then placed in a tube furnace, heated to 700-800° C. under an argon atmosphere, and maintained for 2-3 hours; after the reaction is completed, the product is cleaned with distilled water and anhydrous ethanol, and vacuum dried to obtain a Co / C nanocomposite material; (3) immersing the Co / C nanocomposite material into a hydrochloric acid solution, stirring at 60° C. to 80° C. for 6 to 8 hours to completely dissolve the Co nanosheets, centrifuging and washing to remove impurities, and vacuum drying to obtain carbon nanocages; (4) mixing the carbon nanocage and the pore-forming agent uniformly, placing them in a tube furnace, heating them to 800-900° C. in an argon atmosphere, and maintaining the temperature for 1-2 hours to fully pyrolyze the pore-forming agent and etch the carbon nanocage to obtain a porous carbon nanocage; 2. Preparation of porous carbon nanocages coated with perfluorosulfonic acid ionomers: (1) Weighing a porous carbon nanocage and a Nafion solution and placing them in a beaker, stirring at a temperature of 40 to 60° C. to fully mix the carbon nanocage and the perfluorosulfonic acid ionomer in the Nafion solution, and continuing to stir until the solvent in the Nafion solution is completely volatilized to obtain a solid mixture; (2) placing the solid mixture in a tube furnace in an argon atmosphere and treating it at a temperature of 130 to 150° C. for 2 to 3 hours to coat the carbon nanocage with the perfluorosulfonic acid ionomer, thereby obtaining a porous carbon nanocage coated with the perfluorosulfonic acid ionomer; 3. Preparation of hydroxyl functionalized ionic liquid 1-(2-hydroxyethyl)-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt: (1) Methylimidazole and 2-bromoethanol are mixed evenly at a molar ratio of 1:(1-1.2), added into a round-bottom flask, refluxed at 80-82° C. for 20-24 h, then the product is washed with ether to remove unreacted 2-bromoethanol, and then placed in an oven at 60° C. to 80° C. to dry for 40-48 h, to obtain an intermediate product, 1-(2-hydroxyethyl)-3-methylimidazolium bromide; (2) lithium bis(trifluoromethanesulfonyl)imide and the intermediate product are weighed at a molar ratio of 1:1; lithium bis(trifluoromethanesulfonyl)imide and the intermediate product are respectively prepared into aqueous solutions; the aqueous solution of lithium bis(trifluoromethanesulfonyl)imide is then added to the aqueous solution of the intermediate product, and an ion exchange reaction is carried out at room temperature for 20 to 24 hours to obtain a mixture of ionic liquid and water; extraction is performed to separate the ionic liquid from the water in the mixture, and the ionic liquid is then washed with deionized water, and vacuum dried at room temperature for 24 to 48 hours to obtain a hydroxyl-functionalized ionic liquid 1-(2-hydroxyethyl)-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt; 4. Preparation of Pt / C Catalyst Impregnated with Hydroxyl Functionalized Ionic Liquid: (1) dispersing the hydroxyl-functionalized ionic liquid 1-(2-hydroxyethyl)-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt in isopropanol to prepare a 4-5 mg / mL ionic liquid solution; (2) weighing a Pt / C catalyst and adding it to a beaker, then adding the ionic liquid solution prepared in step 4 (1), and ultrasonicating for 20 to 30 minutes to obtain a mixture; then stirring the mixture at a temperature of 45 to 55° C. to evaporate the solvent therein, so that the ionic liquid is fully impregnated into the pores of the Pt / C catalyst to obtain a powder; finally, vacuum drying the powder to obtain a Pt / C catalyst impregnated with a hydroxyl-functionalized ionic liquid; 5. Configuration of catalyst slurry: (1) Weighing a Pt / C catalyst impregnated with a hydroxyl-functionalized ionic liquid and a porous carbon nanocage coated with a perfluorosulfonic acid ionomer and placing them in a slurry dispersion tube, and adding an appropriate amount of deionized water to wet the catalyst and the porous carbon nanocage; (2) adding Nafion solution and isopropanol to the slurry dispersion tube, and dispersing the mixture for 20 to 30 minutes using a high-speed shearing device to obtain a uniformly dispersed catalyst slurry; 6. Coating and drying of the catalytic layer: Ultrasonic spraying equipment is used to evenly spray the catalyst slurry on both sides of the proton exchange membrane to prepare the cathode and anode catalyst layers, thereby obtaining a catalyst-coated membrane with high gas transmission and high proton conductivity for fuel cells.

2. The method for preparing a catalyst coated membrane with high gas transmission and high proton conductivity for a fuel cell according to claim 1, characterized in that The pore-forming agent described in step 1 (4) is one or more of ammonium chloride, melamine and cyanamide.

3. The method for preparing a catalyst coated membrane with high gas transmission and high proton conductivity for a fuel cell according to claim 1 or 2, characterized in that In step 2 (1), the mass percentage of perfluorosulfonic acid ionomer in the Nafion solution is 5% to 20%.

4. The method for preparing a catalyst coated membrane with high gas transmission and high proton conductivity for a fuel cell according to claim 1 or 2, characterized in that: In step 2 (1), the mass ratio of the porous carbon nanocage to the perfluorosulfonic acid ionomer in the Nafion solution is 1:(0.5-0.7).

5. The method for preparing a catalyst coated membrane with high gas transmission and high proton conductivity for a fuel cell according to claim 1 or 2, characterized in that: In step five (1), the mass ratio of the Pt / C catalyst impregnated with the hydroxyl functionalized ionic liquid to the porous carbon nanocages coated with the perfluorosulfonic acid ionomer is (2-2.5):

1.

6. The method for preparing a catalyst coated membrane with high gas transmission and high proton conductivity for a fuel cell according to claim 1 or 2, characterized in that: The Pt loading in the cathode catalyst layer in step 6 (1) is 0.15-0.18 mg / cm 2 The Pt loading in the anode catalyst layer is 0.05-0.06 mg / cm 2 .

Citation Information

Patent Citations

  • Method for preparing carbon nano-cage by catalyzing organic ligand by metal ion, prepared carbon nano-cage and application of carbon nano-cage

    CN110272035A

  • Nanocage reconstruction catalyst layer for proton exchange membrane fuel cell as well as preparation method and application of nanocage reconstruction catalyst layer

    CN117039007A